2018
DOI: 10.1016/j.ijhydene.2018.02.113
|View full text |Cite
|
Sign up to set email alerts
|

The effect of TiO2 nanotube morphological engineering and ZnS quantum dots on the water splitting reaction: A theoretical and experimental study

Abstract: a b s t r a c t Ordered arrays of TiO 2 nanotubes with smooth and rippled morphologies were prepared by one-step titanium oxidation in NH 4 F and ethylene glycol solution. The samples were then decorated with ZnS using a microwave-assisted solvothermal method. The experiments under constant or pulsed applied voltage resulted in smooth and rippled TiO 2 material morphologies, respectively. Field emission scanning electron microscopy, incident photonto-current efficiency, linear sweep voltammetry and electrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Photocatalysis is an appealing approach toward tackling environmental and global energy problems. Over the past decade, semiconductor photocatalysts with tailored morphologies have attracted intense research interest in many research fields, such as the photocatalytic degradation of pollutants 51 , water splitting [52][53][54] , and photocatalytic antibacterial fields 55,56 , owing to their many intrinsic shape-dependent properties 57,58 . Additionally, the exposed surfaces appearing on the morphology do not only determine the intrinsic physical and chemical properties, but also provide new technological applications in catalysis, optics, electronics, and magnetics.…”
Section: Semiconductor Materialsmentioning
confidence: 99%
“…Photocatalysis is an appealing approach toward tackling environmental and global energy problems. Over the past decade, semiconductor photocatalysts with tailored morphologies have attracted intense research interest in many research fields, such as the photocatalytic degradation of pollutants 51 , water splitting [52][53][54] , and photocatalytic antibacterial fields 55,56 , owing to their many intrinsic shape-dependent properties 57,58 . Additionally, the exposed surfaces appearing on the morphology do not only determine the intrinsic physical and chemical properties, but also provide new technological applications in catalysis, optics, electronics, and magnetics.…”
Section: Semiconductor Materialsmentioning
confidence: 99%
“…Band gap can be modified according to the lattice constant, composition, and morphology. Pereira et al 19 studied the effect of TiO 2 nanotube morphology with deposited ZnS nanoparticles through a theoretical and experimental approach. The Rietveld refinement showed that it is possible to deposit ZnS along the TiO 2 nanotube, and band structure calculations showed a decrease in the band gap values.…”
Section: Introductionmentioning
confidence: 99%
“…It has received attention for its potential applications in sensing, solar cells, catalysis, electronics, optics and biomedicine. 14 Titanium dioxide nanotubes can be combined with other materials such as other metal oxides [15][16][17] noble metal nanoparticles 18,19 quantum dots 20,21 and carbon nanomaterials 22 to offer improved properties for its variety of applications. Besides, this nanostructure is characterized by their effective electron transfer behavior and highly adsorptive property for organic compounds z E-mail: monica.cerro@udlap.mx due to their abundant adsorption sites.…”
mentioning
confidence: 99%